Association of fibronectin 1 deregulation with tyrosine kinase inhibitor resistance in chronic myeloid leukemia - Tiedemann, Lina; Gorantla, Sivahari Prasad; Ahlf, Philine; Schmidt, Lucie Sophie; Pott, Christiane; Litterst, Merit; Waetzig, Vicki; Nagel, Inga; Ruemenapp, Johanna; von Bubnoff, Nikolas; Cascorbi, Ingolf; Kaehler, Meike (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTherapy of chronic myeloid leukemia (CML) with tyrosine kinase inhibitors (TKIs) targeting the BCR::ABL1 kinase has become a paradigm for precision oncology. Despite the tremendous success of this strategy, with an overall long-term survival rate of 83%, approximately 25% of CML patients experience therapy failure within 5 years of treatment. TKI resistance is multifaceted, involving mutations in BCR::ABL1, but also BCR::ABL1-independent mechanisms. Among them, deregulation of cell adhesion and motility of CML cells has been observed in TKI-resistance. The extracellular matrix protein fibronectin 1 (FN1) has been shown to be deregulated in solid tumors promoting proliferation and metastasis. However, the role of FN1 in hematopoietic neoplasms remains to be fully elucidated. The aim of our study was to gain deeper insights into the role of FN1.MethodsFN1 mRNA and protein levels were analyzed using qPCR and immunoblotting. Transfection was performed using nucleofection or stable transfection, followed by analyses of cell number, proliferation and viability. Cell adhesion was assessed using Matrigel-coated surfaces, and FN1 localization was analyzed using immunofluorescence.ResultsFN1 levels were significantly downregulated in CML cell lines resistant against BCR::ABL1 inhibitors in vitro. SiRNA-mediated FN1 knockdown reduced the cell’s susceptibility to all generations of TKIs employed in treatment of CML, including asciminib. In contrast, the restoration of FN1 expression in TKI-resistant cells re-sensitized the cells to TKI treatment. This effect was also observed in K-562 cells that intrinsically harbor the BCR::ABL1 mutation p. E255K (−35.2%, p < 0.001), as well as in K-562 and Ba/F3 cells after stable transfection of the BCR::ABL1 wild-type or the p. T315I gatekeeper mutation. Clinically, deregulation of FN1 was also observed in peripheral blood cells derived from CML patients.ConclusionOur data indicate that FN1 may serve as a potential therapeutic target to address TKI resistance or as a suitable biomarker for the treatment.